Ein Blick auf die Gesellschaft in Ratiaria (Obermoesien) - Ardevan, Radu (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
A look at the society of Ratiaria (Upper Moesia). An inscription from Timacum Minus is analyzed, which mentions an imperial freedman of Hadrian, P. Aelius Aprio, who became augustal in the colony of Ratiaria. Of his sons, two even entered the ordo decurionum of the colony. Both facts are totally unusual for provincial Roman society, and they highlight a very high social mobility here, in the first part of the 2 nd century AD. It is possible that Timacum Minus originally belonged to Ratiaria.